The one player guessing game: a diagnosis on the relationship between equilibrium play, beliefs, and best responses - Ciril Bosch-Rosa; Thomas Meissner (Experimental Economics, 2020)
Experiments involving games have two dimensions of difficulty for subjects in the laboratory. One is understanding the rules and structure of the game and the other is forming beliefs about the behavior of other players. Typically, these two dimensions cannot be disentangled as belief formation crucially depends on the understanding of the game. We present the one-player guessing game, a variation of the two-player guessing game (Grosskopf and Nagel 2008), which turns an otherwise strategic game into an individual decision-making task. The results show that a majority of subjects fail to understand the structure of the game. Moreover, subjects with a better understanding of the structure of the game form more accurate beliefs of other player's choices, and also better-respond to these beliefs.
Keywords: C91; D12; D84; G11; 330; Guessing game; Strategic thinking; Cognitive sophistication